General Health and Respiration - Anshu Manocha (Archives of Pulmonology and Respiratory Care - Peertechz Publications, 2020)
Medical Science uses the medicines and probiotics for the respiratory diseases.For example for the current novel Corona virus infection management medicines, masks, gloves, goggles, regular hand cleaning and social distancing are being used across the world to prevent and control the spread of respiratory droplet infection. Covid 19 is severe acute respiratory corona virus 2 that is SARS- CoV-2. The most common symptom of novel corona virus infection is fever. The other symptoms are coughing, dyspnoea, myalgia, rhinorrhoea,